Energy-Optimized Consensus Formation Control for the Time-Delayed Bilateral Teleoperation System of UAVs - Hui-yu Sun; Guang-ming Song; Zhong Wei; Ying Zhang (International Journal of Aerospace Engineering)
This paper proposes an energy-optimized consensus formation scheme for the time-delayed bilateral teleoperation system of multiple unmanned aerial vehicles (UAVs) in the obstructed environment. To deal with the asymmetric time-varying delays in aerial teleoperation, the local damping is independently distributed on both sides to enforce consensus formation and force tracking of the master haptic device and the slave UAVs. The stability of the time-delayed aerial teleoperation system is analyzed by the Lyapunov function. In addition, a flux-conserved force field is incorporated into the aerial teleoperation system to guarantee a collision-free consensus formation in the obstructed environment. Moreover, to reduce the communication complexity and energy dissipation of the formation, a top-down strategy of 3D optimal persistent graph is first proposed to optimize the formation topology. Under the optimized topology with environmental constraints, communication complexity and energy dissipation can be minimized while the rigid formation can be maintained and transformed persistently in the obstructed environment. Finally, the human-in-the-loop simulations are performed to validate the effectiveness of the proposed scheme.